IMPLEMENTASI PEMBELAJARAN DARING DENGAN MENGGUNAKAN PENDEKATAN SAINTIFIK BERBANTUAN E-LEARNING PADA KONSEP RELASI DAN FUNGSI UNTUK SISWA MTs NEGERI 1 KOTA CIMAHI - Kiki Amanda; Ratni Purwasih (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
The low understanding of students about relations and functions online learning, therefor need to improve of teaching to students, with implementing online learning with scientific approach assisted by e-learning. The problem formulated is how to implement online learning using scientific approach assisted by e-learning the concept relations and functions for students of MtsN 1 Cimahi City? The aim is to find the implementation of online learning using scientific approach assisted by e-learning the concept relations and functions for students of MtsN 1 Cimahi City. This research was conducted on students class VIII-A MTsN 1 Cimahi City in even semester with 32 students. The method used is descriptive qualitative. The instrument is 5 essay questions. The procedure is initial test, test 1 and 2. The source is the results of student answers and student observation sheets. The scientific approach uses 5 indicators namely observing, asking, reasoning, trying, and communicating. The processing technique is to find the average value of students using Microsoft Excel. The average score of students continued from pretest to test 2, from 39,00,65.00 and 76.23. So be concluded that scientific approach using observing, asking, reasoning, trying, and communicating can improve student’s understanding of the concepts relations and functions.